Laminated polyethylene terephthalate film, release film, and method for producing laminated polyethylene terephthalate film

By controlling the content of Si, Ti and Ba components and the structure of the surface layer in the laminated polyethylene terephthalate film, the problem of difficult to control the surface roughness of the film in the prior art is solved, and high recycling is achieved and low surface roughness effects.

CN119451817APending Publication Date: 2025-02-14TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380049970.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-22
Publication Date
2025-02-14

Smart Images

  • Figure BDA0005210543590000381
    Figure BDA0005210543590000381
  • Figure BDA0005210543590000391
    Figure BDA0005210543590000391
  • Figure BDA0005210543590000401
    Figure BDA0005210543590000401
Patent Text Reader

Abstract

A laminated polyethylene terephthalate film comprising a surface layer A and a surface layer B, the laminated polyethylene terephthalate film containing at least one of Si, Ti, and Ba components, the total amount of Si element, Ti element, and Ba element being 0.1 ppm to 5000 ppm (inclusive) per 100 parts by mass of the laminated polyethylene terephthalate film, the surface layer A is a layer in which a functional layer is laminated, the surface layer A has a three-dimensional center plane average surface roughness (SRa) of 1-7 nm (inclusive), and the surface layer A has a maximum peak height (SRp) of 200 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated polyethylene terephthalate film, a release film, and a method for producing the laminated polyethylene terephthalate film. In particular, the present invention relates to a laminated polyethylene terephthalate film useful as a substrate (hereinafter sometimes referred to as an engineering film) used on the basis of providing a functional layer and a method for producing the same. Background Art

[0002] Films having functional layers with various functions on the surface of a base film such as a synthetic resin are used in fields such as electronic components, optical components, labels, and mold release. Films that have been used, films that are out of specification, and films that are damaged during circulation are usually discarded (hereinafter, such films are sometimes referred to as films scheduled to be discarded).

[0003] Patent Document 1 discloses a method for measuring the amount of impurities in a used film, a method for recycling the used film, and a method for converting the recycled raw material into a film.

[0004] For example, Patent Document 1 discloses that a silicone-containing release layer, barium titanate, and a binder formed on the surface of a base film are removed as residues.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-115862 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] For the effective use of resources, it is preferred to recycle the discarded films. In particular, the circulation of laminated films having a functional layer and a substrate, such as a substrate film for mold release, has been increasing in recent years, and the amount of waste has also increased, and further, it is required to circulate and recycle the films for mold release.

[0010] In addition, in the construction of a circulation type recycling, the recycling yield becomes an important item. For example, Patent Document 1 discloses a recycling technology related to a thin film.

[0011] The technology of Patent Document 1 has the following tendency: the recycling yield varies depending on the amount of impurities contained in the film, and the recycling yield deteriorates as the amount of impurities increases. For example, the technology of Patent Document 1 applies thermal recycling when the impurity amount of the film is 0.2 wt% or more when the weight of the entire film is 100 wt%, and the recycling yield is 0 at this time.

[0012] Furthermore, from the viewpoint of transfer to the surface of a processed product, the surface roughness of a release film is always required to be low, and this also applies to recycled films.

[0013] However, in the technology of Patent Document 1, although there is a description about the amount of impurities, there is no description about the surface roughness of the thin film, and there is a concern that the desired surface roughness may not be satisfied.

[0014] Therefore, an object of the present invention is to provide a laminated polyethylene terephthalate film, a method for producing the same, and a release film capable of suppressing the transfer of the surface shape to a processed product. Some preferred embodiments of the present invention relate to a laminated polyethylene terephthalate film having a low surface roughness obtained from a discarded film, particularly a laminated film, for example, a raw material recovered from a release substrate film. In these preferred embodiments, the present invention can provide a laminated polyethylene terephthalate film having an excellent recycling yield and a low surface roughness by containing Si components, Ti components, and Ba components under specific conditions, compared to the impurity amounts of these components contained in the conventional film.

[0015] Solutions for solving problems

[0016] The present inventors conducted intensive studies to solve the above-mentioned problems and found that, in a recycled film, the surface roughness was successfully controlled within a specified range in a system containing impurities of Si, Ti and Ba components, thereby solving the above-mentioned problems and completing the present invention.

[0017] More specifically, in recent years, the need for environmental load reduction activities, such as SDGs and carbon neutrality, has further increased. Therefore, the inventors of the present application have conducted in-depth research on improving the recycling yield of engineering films such as release films, and found that in order to improve the recycling yield of engineering films, it is necessary to control the recycling process of the engineering films among various factors.

[0018] However, for example, if the recycling yield is simply increased, the properties originally required for a release film or the like may become insufficient.

[0019] Therefore, when a laminated polyethylene terephthalate film is used for an engineering film such as a release film (base material in a release film), it is necessary to achieve a balanced improvement in the releasability of the processed product and suppression of the transfer of the surface shape of the engineering film (base material) to the processed product.

[0020] Additionally, it is required to recycle the film containing the particles.

[0021] In view of such a situation, the inventors of the present application discovered that, for example, even an engineering film reproduced from a resin obtained by recycling a film containing particles can have a good balance between maintaining good peelability and suppressing transfer of surface shape, thereby developing the laminated polyethylene terephthalate film of the present invention and its manufacturing method.

[0022] The present invention provides the following aspects.

[0023] [1] A laminated polyethylene terephthalate film comprising a surface layer A and a surface layer B,

[0024] The laminated polyethylene terephthalate film contains one or more of Si, Ti and Ba components,

[0025] Relative to 100 parts by mass of the aforementioned laminated polyethylene terephthalate film, the total amount of Si element, Ti element and Ba element is greater than 0.1 ppm and less than 5000 ppm, the aforementioned surface layer A is a layer of a laminated functional layer, the three-dimensional center plane average surface roughness (SRa) of the aforementioned surface layer A is greater than 1 nm and less than 7 nm, and the maximum peak height (SRp) of the aforementioned surface layer A is less than 200 nm.

[0026] [2] The laminated polyethylene terephthalate film according to [1], comprising 5% by mass or more and 50% by mass or less of a resin obtained by material recycling and / or chemical recycling of a laminated film having a functional layer.

[0027] [3] The laminated polyethylene terephthalate film according to [1] or [2], wherein the laminated polyethylene terephthalate film contains SiO2 having a longest side length of not less than 0.5 μm and not less than 5.0 μm.

[0028] [4] The laminated polyethylene terephthalate film according to any one of [1] to [3], wherein

[0029] The surface layer B is a layer forming the surface of the laminated polyethylene terephthalate film opposite to the surface on which the functional layer is laminated.

[0030] The surface layer B contains at least one particle selected from calcium carbonate particles or silicon dioxide particles in a total amount of 3000 ppm or more and 15000 ppm or less relative to 100 parts by mass of the laminated polyethylene terephthalate film.

[0031] The three-dimensional center plane average surface roughness (SRa) of the surface layer B is 20 nm or more and 40 nm or less.

[0032] [5] The laminated polyethylene terephthalate film according to any one of [1] to [4], wherein the intrinsic viscosity (IV) is 0.500 dl / g or more and 0.700 dl / g or less.

[0033] [6] The laminated polyethylene terephthalate film according to any one of [1] to [5], wherein the thickness ratio of the surface layer A is 30% or more and 50% or less of all layers.

[0034] [7] A release film comprising:

[0035] The laminated polyethylene terephthalate film according to any one of [1] to [6]; and

[0036] The functional layer provided on the surface layer A of the laminated polyethylene terephthalate film,

[0037] The aforementioned functional layer is a release layer.

[0038] [8] A method for producing a laminated polyethylene terephthalate film according to any one of [1] to [6], comprising the following steps:

[0039] (Step 1) A pulverizing step including the step of pulverizing the laminated film having the functional layer to form a pulverized product.

[0040] (Step 2) A chipping step, which includes the step of chipping the pulverized product obtained in the above-mentioned step 1 into recycled chips.

[0041] (Step 3) A step of forming a recycled film, which includes forming the recycled small pieces obtained in the above-mentioned step 2 into a film and winding the above-mentioned film.

[0042] Effects of the Invention

[0043] According to the present invention, a laminated polyethylene terephthalate film having the ability to suppress transfer of the surface shape of a processed product can be provided. In addition, the present invention can provide a laminated polyethylene terephthalate film that can suppress transfer of the surface shape of a processed product even when a recycled resin obtained by material recycling and / or chemical recycling of a film having particles containing at least one of Si, Ti, and Ba is used. DETAILED DESCRIPTION

[0044] Hereinafter, the present invention will be described in detail.

[0045] The laminated polyethylene terephthalate film of an embodiment of the present invention (hereinafter sometimes referred to as "the laminated polyethylene terephthalate film of the present invention") relates to a laminated polyethylene terephthalate film, which contains one or more Si, Ti, and Ba components, the polyethylene terephthalate film contains the aforementioned Si, Ti, and Ba components in a total amount of 0.1 ppm or more and 5000 ppm or less relative to 100 parts by mass of the film, the surface layer A is a layer of a laminated functional layer, the three-dimensional center plane average surface roughness (SRa) is 1 nm or more and 7 nm or less, and the maximum peak height (SRp) is 200 nm or less.

[0046] Here, the total amount of Si, Ti and Ba components refers to the total amount of Si element, Ti element and Ba element. This total amount can be measured by the method described in the examples described later.

[0047] The laminated polyethylene terephthalate film according to the embodiment of the present invention can also be expressed as follows.

[0048] A laminated polyethylene terephthalate film comprises a surface layer A and a surface layer B, wherein the laminated polyethylene terephthalate film comprises one or more of Si, Ti and Ba components, and the total amount of Si element, Ti element and Ba element is greater than 0.1 ppm and less than 5000 ppm relative to 100 parts by mass of the laminated polyethylene terephthalate film, the surface layer A is a layer of a laminated functional layer, the three-dimensional center plane average surface roughness (SRa) of the surface layer A is greater than 1 nm and less than 7 nm, and the maximum peak height (SRp) of the surface layer A is less than 200 nm.

[0049] Since the laminated polyethylene terephthalate film contains one or more of Si, Ti and Ba components, it can be produced using recycled resins (for example, resins obtained by recycling silicone-based release films, resins obtained by recycling release films used in the manufacture of ceramic green sheets), and thus can contribute to reducing environmental load. This is explained. In the case where the laminated polyethylene terephthalate film is produced using a silicone-based release film, that is, a resin obtained by recycling a laminated film having a silicone-based release layer (for example, material recycling, chemical recycling), the laminated polyethylene terephthalate film sometimes contains Si components derived from the silicone-containing release layer. On the other hand, when a laminated polyethylene terephthalate film is produced using a resin obtained by recycling a release film used in the manufacture of a ceramic green sheet containing barium titanate (e.g., material recycling, chemical recycling), the laminated polyethylene terephthalate film sometimes contains a Ti component and a Ba component derived from the barium titanate remaining in the release film. Of course, the laminated polyethylene terephthalate film sometimes also contains an Si component derived from the release film used in the manufacture of the ceramic green sheet. In this way, when a laminated polyethylene terephthalate film is produced using a recycled resin, the laminated polyethylene terephthalate film sometimes contains one or more of the Si, Ti, and Ba components. Since the laminated polyethylene terephthalate film of the present invention contains one or more of the Si, Ti, and Ba components, it can be produced using such a recycled resin (e.g., a resin obtained by recycling a silicone-based release film, a resin obtained by recycling a release film used in the manufacture of a ceramic green sheet). Therefore, the laminated polyethylene terephthalate film of the present invention can contribute to reducing environmental load. It should be noted that the laminated polyethylene terephthalate film of the present invention is preferably produced using recycled resin, but it may be produced without using recycled resin.

[0050] Furthermore, since the upper limit of the total amount of Si element, Ti element and Ba element is 5000 ppm, the recycled resin that can be used in the manufacture of the laminated polyethylene terephthalate film can contain these components to a certain extent. That is, the recycled resin that can be used in the manufacture of the laminated polyethylene terephthalate film is allowed to contain these components to a certain extent. Therefore, the recycling yield can be improved (refer to Patent Document 1), specifically, the recycling yield of the recycled resin that can be used in the manufacture of the laminated polyethylene terephthalate film can be improved.

[0051] Furthermore, since the three-dimensional center plane average surface roughness (SRa) of the surface layer A is 7 nm or less and the maximum peak height (SRp) is 200 nm or less, it is possible to avoid excessive unevenness on the surface of a processed product (e.g., a resin sheet such as a ceramic green sheet) manufactured using a laminated polyethylene terephthalate film. For example, when a ceramic green sheet is manufactured using a release film including a laminated polyethylene terephthalate film and a release layer, it is possible to avoid excessive unevenness on the surface of the ceramic green sheet. That is, it is possible to suppress the transfer of the surface shape to the ceramic green sheet.

[0052] In one embodiment, a laminated film having a functional layer (hereinafter sometimes referred to as a "film having a functional layer". In particular, when the functional layer is a release layer, it is sometimes referred to as a "release film having a functional layer".) contains 5% by mass or more and 50% by mass or less of a resin that has been recycled and / or chemically recycled. Here, the "laminated film having a functional layer" includes a substrate (hereinafter sometimes referred to as a "film substrate", "substrate film", etc.) and a functional layer.

[0053] In addition, in this specification, material recycling and / or chemical recycling may be simply referred to as recycling. In addition, as a representative example, it may be described as material recycling.

[0054] Hereinafter, the structure of the laminated polyethylene terephthalate film for mold release applications (typically, for base film applications of mold release films) will be described, but the laminated polyethylene terephthalate film is not limited to this structure. That is, the laminated polyethylene terephthalate film can be used for other applications.

[0055] In addition, various aspects are listed below, and these aspects can be combined appropriately.

[0056] (Laminated polyethylene terephthalate film)

[0057] The laminated polyethylene terephthalate film for mold release has a surface layer A and a surface layer B (sometimes simply referred to as a laminated film).

[0058] The surface layer A is a layer on which the functional layer is laminated, and the surface layer B is a layer forming the surface opposite to the surface on which the release layer is laminated in the laminated polyethylene terephthalate film.

[0059] In one embodiment, the laminated polyethylene terephthalate film of the present invention comprises a resin obtained by materially and / or chemically recycling a film having a functional layer. The film having a functional layer may be a release film, for example, a used release film (hereinafter sometimes referred to as a used film having a functional layer).

[0060] The used film refers to, for example, a release film formed on a release layer, a release object is laminated thereon, and the release object is peeled off from the release layer.

[0061] The used release film may include release films that have been stored for a long period of time without being used after production, release films that have not been used due to reasons such as not satisfying required properties, and release films that cannot achieve their original purpose such as cut ends.

[0062] In one embodiment, the laminate film having a functional layer is a release film for molding a resin sheet containing an inorganic compound. Examples of the inorganic compound include metal particles, metal oxides, minerals, and calcium carbonate, silica particles, aluminum particles, and barium titanate particles.

[0063] Examples of the resin contained in the resin sheet include polyvinyl acetal resin and poly(meth)acrylate resin.

[0064] For example, the laminated film with a functional layer is used for the manufacture of resin sheets requiring high smoothness such as semiconductor components, ceramic green sheets, and optical films. By recycling the laminated film used for such purposes, the various physical properties such as haze and surface roughness in the present invention can be more effectively shown. In addition, the laminated film (release film) with a functional layer used for such purposes preferably contains particles in order to show windability while maintaining smoothness.

[0065] For example, as described later, the functional layer may contain a resin such as a silicone-based, cyclic olefin-based, acyclic olefin-based, fluorine-based, alkyd-based, acrylic-based, melamine-based, or epoxy-based resin.

[0066] The laminated film with a functional layer for material and / or chemical recycling is a film having a functional layer provided on at least one surface of a base film containing a thermoplastic resin. The base film is preferably a polyester film, for example, a laminated polyethylene terephthalate film for mold release having at least a surface layer A and a surface layer B of the present invention.

[0067] That is, the present invention allows the release laminated polyethylene terephthalate film of the present invention to be recycled a plurality of times and is therefore suitable for effective utilization of resources required in a recycling-oriented society.

[0068] The present invention may further utilize components other than the polyester component without departing from the scope of the present invention.

[0069] The raw materials and the like are not particularly limited as long as they are within the scope of the present invention.

[0070] Particularly preferably, a resin obtained by materially and / or chemically recycling a laminated film having a functional layer directly laminated on a substrate can be used. By using a laminated film having a functional layer directly laminated on a substrate, a substrate with fewer impurities can be recycled, so the haze and surface roughness of the present invention can be obtained more effectively.

[0071] As the material of the polyester film included in the substrate, polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polycyclohexanedimethanol terephthalate, etc. can be used without particular limitation.

[0072] The base film may be made of a single material, a mixed system such as a polymer alloy, or a structure in which a plurality of raw materials are laminated.

[0073] In one embodiment, the polyester resin contained in the polyester film is preferably an aromatic polyester obtained by polycondensation of a diol component and an aromatic dicarboxylic acid component from the viewpoint of reducing mechanical properties and surface defects. Examples of the aromatic dicarboxylic acid component include terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, and 6,6'-(ethylenedioxy)di-2-naphthoic acid, and examples of diol components include ethylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, and 1,6-hexanediol. Among these, ethylene terephthalate or ethylene 2,6-naphthalene dicarboxylic acid is preferably used as the main repeating unit from the perspective of dimensional stability during processing at high temperatures, and ethylene 2,6-naphthalene dicarboxylic acid is particularly preferably used as the main repeating unit. From the viewpoint of further improving dimensional stability against environmental changes, copolymers of 6,6'-(ethylenedioxy)di-2-naphthoic acid components, 6,6'-(trimethylenedioxy)di-2-naphthoic acid components, and 6,6'-(butylenedioxy)di-2-naphthoic acid components described in International Publication No. 2008 / 096612 are also preferred.

[0074] In polyethylene terephthalate, the repeating unit of ethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and other dicarboxylic acid components and glycol components may be copolymerized in small amounts, but from the perspective of cost, it is preferably manufactured only from terephthalic acid and ethylene glycol. In addition, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc. may also be added within the range that does not hinder the effect of the film of the present invention. From the reasons such as high bidirectional elastic modulus, the polyester film is preferably a stretched polyester film.

[0075] The laminated polyethylene terephthalate film of the present invention preferably contains particles. For example, it may contain one or more inorganic particles or organic particles.

[0076] The particles contained are not limited to specific inorganic particles and organic particles, and for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, and organic polymer particles such as styrene, acrylic acid, melamine, benzoguanamine, and silicone can be listed. It can also be a film that is combined and added with more than two kinds. It is preferred to contain titanium oxide, calcium carbonate, and silicon dioxide with high versatility.

[0077] For example, a laminated film having a functional layer for material and / or chemical recycling may contain the above particles. In addition, a polyester resin composition as a raw material for a laminated polyethylene terephthalate film may contain the above particles.

[0078] For example, a laminated film having a functional layer for material and / or chemical recycling, or a polyester resin composition as a raw material of the laminated polyethylene terephthalate film of the present invention may contain the above-mentioned particles under the following conditions.

[0079] In one embodiment, the raw material of the laminated polyethylene terephthalate film of the present invention may be a resin composition obtained by recycling a base material portion of a laminated film having a functional layer, for example, a polyester resin composition.

[0080] The average particle size of the particles contained in the polyester resin composition of the present invention is preferably 0.2 μm or more and 5.0 μm or less, and more preferably 0.4 μm or more and 5.0 μm or less. When it is 0.2 μm or more, air can be uniformly released when the film is wound into a roll, and the winding shape is good and the planarity is good, which is suitable for the manufacture of ultra-thin ceramic green sheets, and is therefore preferred (hereinafter referred to as good operability). When it is 5.0 μm or less, the surface unevenness becomes smaller, and there is no transfer to the processed product (such as semiconductor components, ceramic green sheets, optical films), which is preferred.

[0081] The content of particles is preferably 100 ppm or more and 10,000 ppm or less, and more preferably 300 ppm or more and 8,000 ppm or less relative to the laminated polyethylene terephthalate film. When it is 100 ppm or more, the handling property is good and it is preferred. When it is 10,000 pppm or less, there is no transfer to the processed product and it is preferred.

[0082] Even when the laminated film with a functional layer for material and / or chemical recycling, or the polyester resin composition as a raw material of the laminated polyethylene terephthalate film of the present invention does not contain particles, the laminated polyethylene terephthalate film of the present invention can be obtained. In this embodiment, for example, particles under the conditions described in this specification can be added in the recycling step of the film with a functional layer.

[0083] The mold release laminated polyethylene terephthalate film in the present invention may be a biaxially stretched laminated polyethylene terephthalate film.

[0084] The intrinsic viscosity (IV) of the laminated polyethylene terephthalate film for mold release in the present invention, for example, the biaxially stretched laminated polyethylene terephthalate film, is preferably 0.500 dl / g to 0.700 dl / g, for example, 0.510 dl / g to 0.650 dl / g, more preferably 0.510 dl / g to 0.620 dl / g, and particularly preferably 0.510 dl / g to 0.580 dl / g.

[0085] When the intrinsic viscosity is 0.500 dl / g or more, breakage is less likely to occur during the stretching step, which is preferred. In addition, biaxial stretching can be performed without impairing film forming properties.

[0086] Furthermore, when the weight is below 0.700 dl / g, the cutting property when cutting into a specified product width is good and no dimensional defect occurs, so it is preferred. In addition, the filter filtration pressure can be suppressed and the operability is not hindered. The raw material is preferably fully vacuum dried.

[0087] The laminated polyethylene terephthalate film of the present invention, for example, a biaxially stretched polyester film, is also expected to show the above-mentioned intrinsic viscosity in the form of a film obtained by thinning recycled small pieces.

[0088] In one embodiment, if the laminated polyethylene terephthalate film of the present invention comprises a resin obtained by materially and / or chemically recycling a film having a functional layer containing one or more inorganic particles or organic particles, the intrinsic viscosity (IV) can satisfy the condition of being greater than 0.50 dl / g and less than 0.70 dl / g, preferably greater than 0.51 dl / g and less than 0.58 dl / g.

[0089] The present invention should not be limited to a specific theory, but it is speculated that by making the recycled resin contain particles, the problem of prolonged cooling time and quality degradation during film making can be suppressed, and the temperature unevenness during film making can be suppressed. In addition, it is speculated that it also helps to improve the smoothness of the surface shape of the obtained film.

[0090] Therefore, the surface roughness SRa of the present invention can be brought into a predetermined range, and for example, a laminated polyethylene terephthalate film having excellent handleability and low surface roughness can be obtained.

[0091] The thickness of the laminated polyethylene terephthalate film of the present invention is preferably 12 to 100 μm, more preferably 12 to 85 μm, and more preferably 15 to 80 μm. When the thickness of the film is 12 μm or more, there is no worry about deformation due to heat during film production or when used as an engineering film, which is preferred. On the other hand, if the thickness of the film is 100 μm or less, the amount of film discarded after use will not increase extremely, which is preferred in terms of reducing environmental load, and further, the material per unit area of ​​the release film used becomes less, so it is also preferred from an economic point of view.

[0092] In one embodiment, the thickness ratio of the surface layer A is 30% to 50% of all layers. That is, the thickness of the surface layer A is preferably 30% to 50% of the thickness of the laminated polyethylene terephthalate film (100%).

[0093] The laminated polyethylene terephthalate film of the present invention contains one or more Si, Ti, and Ba components, and the polyethylene terephthalate film contains Si, Ti, and Ba components in a total amount of 0.1 ppm to 5000 ppm based on 100 parts by mass of the film.

[0094] The laminated polyethylene terephthalate film for mold release has a surface layer A and a surface layer B, and may further have a core layer C. The core layer C may be disposed between the surface layer A and the surface layer B, and the core layer C may have a multi-layered structure.

[0095] Furthermore, at least one of the surface layer A, the surface layer B, and the core layer C may contain one or more Si, Ti, and Ba components, or all the layers may contain one or more Si, Ti, and Ba components.

[0096] In one embodiment, the layer configuration in the thickness direction may be a stacked structure of A / B, a stacked structure of A / C / B, or the like.

[0097] The laminated polyethylene terephthalate film in the present invention includes a surface layer A substantially free of particles having a particle size of 1.0 μm or more and a surface layer B containing particles. Preferably, the surface layer A substantially does not contain inorganic particles having a particle size of 1.0 μm or more.

[0098] In this embodiment, particles having a particle size of less than 1.0 μm and 1 nm or more may exist in the surface layer A. By making the surface layer A substantially free of particles having a particle size of 1.0 μm or more, such as inorganic particles, it is possible to reduce the possibility of the particle shape in the substrate being transferred to the resin sheet and causing problems.

[0099] In one embodiment, the surface layer A also does not contain particles having a particle diameter of less than 1.0 μm, thereby more effectively suppressing the transfer of the particle shape in the substrate to the resin sheet and the generation of a defect.

[0100] In one embodiment, the mold release laminated polyethylene terephthalate film of the present invention is preferably a laminated film having a surface layer A substantially free of inorganic particles on at least one surface. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet to cause a problem.

[0101] For example, a preferred embodiment is one in which the surface layer A substantially does not contain particles having a particle size of less than 1.0 μm and also substantially does not contain particles having a particle size of 1.0 μm or more.

[0102] Here, in the present invention, "substantially free of particles" means, for example, in the case of inorganic particles smaller than 1.0 μm, when the inorganic elements are quantified by fluorescent X-ray analysis, the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit. This is because, even if particles are not actively added to the film, sometimes contaminant components originating from foreign matter, dirt attached to the production line and / or equipment in the manufacturing process of the raw resin or film will be peeled off and mixed into the film. In addition, "substantially free of particles with a particle size of 1.0 μm or more" means that particles with a particle size of 1.0 μm or more are not actively included.

[0103] In one embodiment, the surface layer A preferably does not contain particles of lubricant or the like and does not use recycled raw materials, so that the surface roughness can be reduced more effectively.

[0104] The surface layer B may be coated with a coating layer containing a binder for forming the surface layer B during film formation.

[0105] From the viewpoint of the slipperiness of the film and the ease of air release, the surface layer B preferably contains at least one type of particles selected from calcium carbonate particles and silica particles.

[0106] The content of the particles contained is preferably 500 to 20,000 ppm in the entire layer.

[0107] Particularly, the surface layer B may contain 500 to 15000 ppm of particles, for example, 3000 ppm to 15000 ppm of particles.

[0108] In one embodiment, the surface layer B contains 500 to 10,000 ppm of silica particles and / or calcium carbonate particles. By making the surface layer B contain silica particles and / or calcium carbonate particles within the above range, all layers of the laminated polyethylene terephthalate film of the present invention also contain 500 to 10,000 ppm of silica particles and / or calcium carbonate particles.

[0109] Here, in the present invention, when describing the content of particles contained in all layers or describing them in the same meaning, it means the total amount of particles contained in the entire surface layer A, surface layer B and core layer C provided as required.

[0110] The surface layer A is a layer on which the functional layers are stacked, and has a three-dimensional center plane average surface roughness (SRa) of 1 nm to 7 nm, and preferably has a maximum peak height (SRp) of 200 nm or less.

[0111] By having such a three-dimensional center plane average surface roughness and maximum peak height, it is possible to suppress surface irregularities and to suppress the transfer of irregularities to a processed product, that is, a molded product.

[0112] The average surface roughness (SRa) of the surface layer A is preferably 1.5 nm to 6.5 nm, for example 2.0 nm to 6.0 nm. By making the average surface roughness (SRa) of the surface layer A within the above range, high smoothness can be achieved for the functional layers stacked on the surface layer A, such as the release layer.

[0113] For example, by controlling the amount of Si, Ti, and Ba components present in the surface layer A, the three-dimensional center plane average surface roughness (SRa) and the maximum peak height (SRp) of the surface layer A can be set within the scope of the present invention. Preferably, the total amount of Si, Ti, and Ba components contained in the surface layer A refers to a content that is less than 50 ppm, preferably less than 10 ppm, and most preferably less than the detection limit when the inorganic elements are quantified by fluorescent X-ray analysis.

[0114] In addition, even if Si, Ti, and Ba components are not actively added to the surface layer A, it is assumed that the total amount of Si, Ti, and Ba components is less than 50 ppm when the inorganic elements are quantified by fluorescent X-ray analysis for the surface layer A. This is because, for example, contaminant components originating from foreign matter, dirt attached to the production line and / or equipment in the manufacturing process of the raw resin or film may be peeled off and mixed into the film.

[0115] For example, the three-dimensional center plane average surface roughness (SRa) of the surface layer B can be greater than 20nm and less than 40nm. In addition, the surface layer B can also show a maximum peak height (SRp) within the above range. In one embodiment, at least one of the surface roughness (SRa) or the maximum peak height (SRp) of the surface layer A and the surface layer B shows a different numerical range.

[0116] When the particle content in the laminated polyethylene terephthalate film is 500ppm or more and the SRa of at least the surface layer A is 1nm or more, no matter in which case of the film production or use, when the film is rolled into a roll, air can be uniformly released, the winding shape is good, and the planarity is also good. Therefore, it is suitable for the manufacture of ultra-thin layer ceramic green sheets. When the total particle content of the laminated polyethylene terephthalate film is less than 10000ppm and the SRa of at least the surface layer A is less than 7nm, the surface unevenness can be suppressed and the unevenness transfer to the molded product can be prevented.

[0117] In one embodiment, a resin layer substantially free of inorganic particles, such as a polyester resin layer, may be provided on the functional layer side of the surface layer A, or a resin layer substantially free of particles having a particle size of 1.0 μm or more, such as a polyester resin layer, may be provided on the functional layer side of the surface layer A.

[0118] The maximum peak height (SRp) of the surface layer A is 200 nm or less. In one embodiment, the maximum peak height (SRp) of the surface layer A is 20 nm or more and 200 nm or less, and may be 25 nm or more and 180 nm or less.

[0119] By setting the maximum peak height (SRp) to 200 nm or less, the surface irregularities become smaller and transfer to a processed product can be suppressed.

[0120] The core layer C is a layer in which the surface layer A is laminated on one surface and the surface layer B is laminated on the opposite surface.

[0121] The surface shape of the core layer C may contain one or more Si, Ti, and Ba components, and may show the content specified in the present invention. In addition, particles may be appropriately added to control the surface shape.

[0122] In one embodiment, the core layer C of the present invention may include materials and / or chemically recycled resins.

[0123] For example, the present invention is a laminated polyethylene terephthalate film, which uses a raw material obtained by recycling a film having a functional layer, contains at least one of Si, Ti, and Ba components, and contains each component in a total of 0.1 ppm or more. Furthermore, it is preferred that the three-dimensional center plane average surface roughness (SRa) of the polyester film surface is 1 nm or more and 7 nm or less, for example, SRa is 1.5 nm or more and 6.5 nm or less, and the maximum peak height (SRp) is 200 nm or less.

[0124] The laminated polyethylene terephthalate film contains one or more Si, Ti, and Ba components, and the polyethylene terephthalate film contains the Si, Ti, and Ba components in a total amount of 0.1 ppm or more and 5000 ppm or less relative to 100 parts by mass of the film. Preferably, the total amount of Si, Ti, and Ba components contained is 0.3 ppm or more and 3000 ppm or less, for example, 0.3 ppm or more and 1000 ppm or less.

[0125] By making the total content of Si, Ti and Ba components (i.e., the total amount of Si element, Ti element and Ba element) within the above range, the operability of, for example, a laminated polyethylene terephthalate film becomes good, and the unevenness on the surface of the film can be suppressed, thereby preventing the transfer of the unevenness to the processed product, i.e., the molded product.

[0126] Here, in the conventional recycled films, there is a tendency to actively remove Si, Ti, and Ba components. On the other hand, in the present invention, it is found that by containing a predetermined amount of these components, the handling properties of the laminated polyethylene terephthalate film can be well maintained, and the unevenness of the film surface can be suppressed, and the unevenness transfer to the molded product can be prevented. In one embodiment, the unevenness of the film surface can be suppressed in units of several nm to several tens of nm, so even when used for molding of extremely thin ceramic green sheets, good processability and peelability can be given to the release film.

[0127] Furthermore, the mechanical properties of the film of the present invention, such as tensile strength and elastic modulus, can also show values ​​comparable to or higher than those of a film made of a virgin material that does not contain recycled resin.

[0128] As described above, the present invention can improve various physical properties of the obtained polyester and exhibit high recyclability by containing Si, Ti, and Ba components in predetermined amounts.

[0129] In one embodiment, when core layer C is provided, core layer C and / or surface layer B contain more than one Si, Ti, Ba components, and the total amount of Si, Ti, Ba components contained in core layer C and / or surface layer B (i.e., the total amount of Si element, Ti element and Ba element) is more than 0.1ppm and less than 5000ppm. Although it should not be limited to a specific theory to explain, surface layer A does not contain Si, Ti, Ba components in substance, and surface layer A not only has high surface smoothness, but also can show high adhesion with functional layer.

[0130] In one embodiment, the content of Si component in the whole laminated polyethylene terephthalate film is 0.3 ppm or more and 2000 ppm or less, for example, 0.3 ppm or more and 1500 ppm or less, and can be 0.3 ppm or more and 1000 ppm or less. In another embodiment, the content of Si component can be 0.3 ppm or more and 500 ppm or less. By making the content of Si component within the above range, for example, the operability of the laminated polyethylene terephthalate film becomes good, and the unevenness of the film surface can be suppressed, and the unevenness transfer to the molded product can be prevented.

[0131] In one embodiment, the core layer C may contain a Si component. Furthermore, the core layer C may contain 5 mass % or more and 50 mass % or less of a resin obtained by recycling a release film having a functional layer, and may contain a Si component within the above range.

[0132] In the present invention, by including 5 mass % or more and 50 mass % or less of a resin obtained by recycling a release film having a functional layer, the content of Si component in the entire laminated polyethylene terephthalate film is made to be 0.3 ppm or more and 2000 ppm or less. Thus, even when the recycled resin is included, the film can exhibit good mechanical properties such as tensile strength, elasticity, surface hardness, and tear strength.

[0133] Here, in the prior art, when the release film having a functional layer is recycled, the silicone component present on the surface of the substrate needs to be almost completely removed. On the other hand, in the present invention, it was found that good mechanical properties can be achieved by making the content of the Si component in the entire laminated polyethylene terephthalate film 0.3 ppm or more and 2000 ppm or less.

[0134] Although the explanation is not limited to a specific theory, it is presumed that the Si component contributes to the formation of the crystal structure of the polyester film.

[0135] In one embodiment, the content of Ti component in the entire laminated polyethylene terephthalate film is greater than 0.3ppm and less than 2000ppm, for example, greater than 0.3ppm and less than 1500ppm, and can be greater than 0.3ppm and less than 1000ppm. By making the content of Ti component within the above range, for example, compared with the case where the Ti component is less than 0.3ppm, the surface roughness (SRa) and the maximum peak height (SRp) of the polyester film can be more controlled in the range of several nm to tens of nm. According to the characteristics required by the release layer stacked on the laminated polyethylene terephthalate film, the surface roughness (SRa) and the maximum peak height (SRp) of the polyester film can be more finely controlled, so that, for example, the processability of the ceramic green sheet can be improved. In addition, the demolding property of the ceramic green sheet can also be improved.

[0136] Similarly, the content of the Ba component is also 0.3 ppm or more and 2000 ppm or less, for example, 0.3 ppm or more and 1500 ppm or less, or 0.3 ppm or more and 1000 ppm or less. The Ba component is also similar to the Ti component, for example, compared with the case where the Ti component is less than 0.3 ppm, the surface roughness (SRa) and the maximum peak height (SRp) of the polyester film can be greatly controlled within the range of several nm to several tens of nm.

[0137] As described above, in the present invention, since predetermined amounts of Ti and Ba components can be contained, for example, a release film used for forming a ceramic green sheet can be recycled and utilized.

[0138] In conventional recycled films, the residues of green sheet components, release layer components, and base material are completely separated, and only high-purity polyester resin is used.

[0139] On the other hand, in the present invention, the total amount of Si, Ti, and Ba components (i.e., the total amount of Si element, Ti element, and Ba element) needs to be within the scope of the present invention, and the residue of the green sheet component, the release layer component, and the base material can be recycled and utilized within the scope of the composition of the present invention. Therefore, in the present invention, for example, the material recycling process of the resin obtained by recycling the release film having a functional layer can be simplified and shortened compared with the past, and the recycling of waste can be promoted more effectively.

[0140] In one embodiment, the laminated polyethylene terephthalate film of the present invention contains a resin obtained by recycling materials (also referred to as a recycled raw material) at 5% by mass or more and 50% by mass or less in 100% by mass of the laminated polyethylene terephthalate film. For example, the recycled raw material is contained at 8% by mass or more and 47% by mass or less, for example, at 10% by mass or more and 45% by mass or less.

[0141] By containing 5 mass % or more and 50 mass % or less, the use amount of petroleum-derived raw materials can be reduced, and it can be said that the film is environmentally friendly.

[0142] The resin obtained by recycling a mold release film having a functional layer can be used. Alternatively, the resin obtained by recycling a mold release film having a functional layer that is to be discarded after use can be used.

[0143] When the laminated polyethylene terephthalate film has a multilayer structure, for example, when the surface layer A has a two-layer structure, the recycled raw materials contained in the surface layer A can be appropriately compounded in such a manner that the total amount in the two layers is 5% by mass or more and 50% by mass or less. Similarly, for example, when the core layer C has a multilayer structure, the recycled raw materials contained in the core layer C can be appropriately compounded in such a manner that the total amount in each layer forming the layer C is 5% by mass or more and 50% by mass or less.

[0144] In the case where the laminated polyethylene terephthalate film includes a recycled resin, as the particles included in the laminated polyethylene terephthalate film, from the viewpoint of transparency and cost, silicon dioxide particles and / or calcium carbonate particles are more preferably used. In addition to silicon dioxide and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles, etc. can also be used. As other inorganic particles that can be used, aluminum oxide-silicon dioxide composite oxide particles, hydroxyapatite particles, etc. can be cited. In addition, as heat-resistant organic particles, cross-linked polyacrylic acid particles, cross-linked polystyrene particles, benzoguanamine particles, etc. can be cited. In addition, in the case of using silicon dioxide particles, preferably porous colloidal silica, in the case of using calcium carbonate particles, from the viewpoint of preventing the lubricant from falling off, preferably a light calcium carbonate surface-treated with a high molecular compound of polyacrylic acid is implemented.

[0145] When the laminated polyethylene terephthalate film contains recycled resin, the length of the longest side of the particles that can be contained is 0.5 μm or more and 5.0 μm or less. For example, the average particle size of the particles is preferably 0.2 μm to 4.0 μm, and more preferably 0.4 μm to 3.6 μm. When it is 0.2 μm or more, the handling property is good and it is preferred. When it is 4.0 μm or less, the surface unevenness becomes small and there is no transfer to the processed product, which is also preferred.

[0146] The content of the particles is preferably 100 to 10,000 ppm, more preferably 300 to 8,000 ppm, relative to the laminated polyethylene terephthalate film. When it is 100 ppm or more, the workability is good and it is preferred. When it is 10,000 pppm or less, the surface irregularities can be suppressed and the irregularities can be prevented from being transferred to the molded product.

[0147] The method for measuring the average particle size of the particles can be carried out by the following method: observe the particles of the cross section of the processed film with a scanning electron microscope, observe 100 particles, and use the average value as the average particle size. As long as the purpose of the present invention is met, the shape of the particles is not particularly limited, and spherical particles and amorphous non-spherical particles can be used. The particle size of amorphous particles can be calculated in the form of equivalent circle diameter. The equivalent circle diameter is the value obtained by dividing the area of ​​the observed particles by pi (π), calculating the square root and multiplying it by 2 times.

[0148] The laminated polyethylene terephthalate film may contain two or more different kinds of particles, or may contain particles of the same kind but with different average particle diameters.

[0149] Examples of methods for adding pellets include side feeding in material recycling, melt-kneading recycled raw materials and pellets to make a masterbatch, and mixing two or more recycled raw materials, but the present invention is not limited to these methods.

[0150] Functionality can also be imparted by coating. The means for providing the coating is not particularly limited, but it is preferably provided by a so-called in-line coating method in which the coating is applied during the film formation of the polyester film.

[0151] In one embodiment, the laminated polyethylene terephthalate film contains SiO 2 having a longest side length of 0.5 μm or more and 5.0 μm or less. Preferably, at least one of the core layer C and the surface layer B contains SiO 2.

[0152] The functional layer of the film with functional layer to be recycled (i.e., the film with functional layer as the raw material of recycled resin) is not particularly limited, and may include resins such as silicone, cyclic olefin, non-cyclic olefin, fluorine, alkyd, acrylic, melamine, and epoxy resins. Preferably, the functional layer includes resins of silicone, acrylic, and melamine. By making the functional layer include these resins, in the laminated polyethylene terephthalate film for demoulding, the adhesion of the surface layer A and the surface layer B can be improved, and in one embodiment, the adhesion of the core layer C to the surface layer A and the surface layer B can be improved, and then a laminated polyethylene terephthalate film for demoulding with high smoothness can be obtained. As the functional layer, an antistatic layer, a demoulding layer, and an adhesive layer can be exemplified.

[0153] In particular, when the functional layer is used as a release layer, residues of the object to be released (i.e., the processed product) may exist on the surface of the release layer. Therefore, in the present invention, a removal step (described later in detail) of removing the attached matter from the film having the functional layer may also be performed.

[0154] For example, as the object to be demolded, there can be mentioned an adhesive, an optical film, a ceramic green sheet, etc., and a part of them may exist as the attached matter of the present invention.

[0155] In addition, the release layer of the present invention is also required to have high adhesion to the object to be released. For example, the release layer for adhesives, the release layer for optical films, and the release layer for ceramic green sheets can be used in the manufacturing process of the object to be released, the manufacturing process of the device using the same, etc., and therefore needs to show high adhesion between these processes.

[0156] In addition, the release layer in the present invention may be a release layer exposed to high temperature (e.g., 60°C or higher) and / or high humidity (e.g., 70% or higher) conditions, or a release layer used under high tension conditions. By including a removal step of removing attached matter from a film having a functional layer (e.g., a release layer used under these conditions), the purity of the recycled substrate can be improved, for example, achieving the required optical properties, mechanical strength, etc.

[0157] The silicone compound refers to a compound having a silicone structure in the molecule, and examples thereof include curable silicones, silicone graft resins, and modified silicone resins such as alkyl-modified silicone resins.

[0158] As the reactive curable silicone resin, an addition reaction curable silicone resin, a condensation reaction curable silicone resin, an ultraviolet or electron beam curable silicone resin, or the like can be used.

[0159] Examples of the silicone resin of the addition reaction system include silicone resins cured by reacting polydimethylsiloxane having a vinyl group introduced at the terminal or side chain with hydrogen siloxane using a platinum catalyst. In this case, it is more preferable to use a resin that can be cured within 30 seconds at 120° C. because processing at low temperatures is possible.

[0160] As examples, there are low-temperature addition curing types (LTC1006L, LTC1056L, LTC300B, LTC303E, LTC310, LTC314, LTC350G, LTC450A, LTC371G, LTC750A, LTC752, LTC755, LTC760A, LTC850, etc.) and thermal UV curing types (LTC851, BY24-510, BY 24-561, BY24-562, etc.), Shin-Etsu Chemical Co., Ltd. solvent addition type (KS-774, KS-882, X62-2825, etc.), solvent addition + UV curing type (X62-5040, X62-5065, X62-5072T, KS5508, etc.), dual-cure curing type (X62-2835, X62-2834, X62-1980, etc.), etc.

[0161] Examples of the condensation reaction silicone resin include silicone resins having a three-dimensional crosslinked structure formed by condensation reaction of polydimethylsiloxane having an OH group at the terminal and polydimethylsiloxane having an H group at the terminal using an organic tin catalyst.

[0162] As UV-curable silicone resins, for example, silicone resins that utilize the same free radical reaction as the most basic type of cross-linking of conventional silicone rubbers; silicone resins that are photocured by introducing unsaturated groups; silicone resins that are cross-linked by decomposing onium salts with ultraviolet rays to generate strong acids, thereby cleaving epoxy groups; silicone resins that are cross-linked by the addition reaction of thiols to vinyl siloxanes, etc. In addition, electron beams can also be used instead of the above-mentioned ultraviolet rays. The energy of electron beams is stronger than that of ultraviolet rays, and free radical-based cross-linking reactions can be performed even without using an initiator as in the case of ultraviolet curing.

[0163] Examples of the resin used include UV-curing silicones manufactured by Shin-Etsu Chemical Co., Ltd. (X62-7028A / B, X62-7052, X62-7205, X62-7622, ​​X62-7629, X62-7660, etc.), UV-curing silicones manufactured by Momentive Performance Materials (TPR6502, TPR6501, TPR6500, UV9300, UV9315, XS56-A2982, UV9430, etc.), and UV-curing silicones manufactured by Arakawa Chemical Industries, Ltd. (Silicolease UV POLY 200, POLY 215, POLY 201, KF-UV 265 AM, etc.).

[0164] As the ultraviolet curing silicone resin, acrylate-modified or glycidoxy-modified polydimethylsiloxane may be used. These modified polydimethylsiloxanes may be mixed with a multifunctional acrylate resin, epoxy resin, etc. and used in the presence of an initiator.

[0165] The cyclic olefin resin contains a cyclic olefin as a polymerizable component. The cyclic olefin is a polymerizable cyclic olefin having an olefinic double bond in the ring, and can be classified into monocyclic olefins, bicyclic olefins, and polycyclic olefins having three or more rings.

[0166] Examples of the monocyclic olefin include cyclic C4-12 cycloolefins such as cyclobutene, cyclopentene, cycloheptene, and cyclooctene.

[0167] Examples of the bicyclic olefin include 2-norbornene; norbornenes having an alkyl group (C1-4 alkyl group) such as 5-methyl-2-norbornene, 5,5-dimethyl-2-norbornene, 5-ethyl-2-norbornene, and 5-butyl-2-norbornene; norbornenes having an alkenyl group such as 5-ethylidene-2-norbornene; norbornenes having an alkoxycarbonyl group such as 5-methoxycarbonyl-2-norbornene and 5-methyl-5-methoxycarbonyl-2-norbornene; norbornenes having a cyano group such as 5-cyano-2-norbornene; norbornenes having an aromatic group such as 5-phenyl-2-norbornene and 5-phenyl-5-methyl-2-norbornene; octahydronaphthalene; octahydronaphthalene having an alkyl group such as 6-ethyl-octahydronaphthalene, and the like.

[0168] Examples of the polycyclic olefin include dicyclopentadiene; derivatives such as 2,3-dihydrodicyclopentadiene, methyl octahydrofluorene, dimethyl octahydronaphthalene, dimethyl cyclopentadienylnaphthalene, and methyl octahydrocyclopentadienylnaphthalene; derivatives having a substituent such as 6-ethyl-octahydronaphthalene; adducts of cyclopentadiene with tetrahydroindene, trimers and tetramers of cyclopentadiene, and the like.

[0169] The non-cyclic olefin resin contains non-cyclic olefin as a polymerizable component. Examples of the non-cyclic olefin include ethylene, propylene, 1-butene, isobutylene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene and the like.

[0170] Rubber may also be used as the resin for surface treatment, for example, copolymers of butadiene, isoprene, etc. may be mentioned.

[0171] Regardless of whether it is a cyclic olefin or a non-cyclic olefin, the olefin-based resin may be used alone or in combination of two or more.

[0172] Cyclic olefin resins and non-cyclic olefin resins may partially have hydroxyl-modified and acid-modified sites, and a crosslinking agent may be used to crosslink these functional groups. The crosslinking agent may be appropriately selected according to the modified group, and examples thereof include aromatic diisocyanates such as toluene diisocyanate, 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylene diisocyanate, polymethylene polyphenyl isocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, lower aliphatic diisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, alicyclic isocyanates such as hydrogenated products of the aforementioned aromatic diisocyanates, and melamine-based crosslinking agents such as methyl etherified melamine resins and butyl etherified melamine resins, and epoxy-based crosslinking agents.

[0173] As a fluorine compound, there is no particular limitation as long as it is a compound having at least any one of a perfluoroalkyl group and a perfluoroalkyl ether group. A portion of the fluorine compound can be modified by an acid, a hydroxyl group, an acrylate group, etc. A crosslinking agent can also be added to crosslink the modified portion. Alternatively, a compound having at least any one of a perfluoroalkyl group and a perfluoroalkyl ether group can be added to a UV curable resin and polymerized. Alternatively, it can also be used in the form of adding a small amount of a compound having a perfluoroalkyl group that does not have a reactive functional group to the binder resin.

[0174] A release agent such as a polyolefin-based release agent, a long-chain alkyl-containing resin-based release agent, a fluorine-based release agent, or a silicone-based release agent can be used as a main resin for the release layer of a release film or can be used as an additive to a binder resin.

[0175] The binder resin is not particularly limited, and for example, UV-curable resins obtained by curing functional groups such as acryloyl, vinyl, and epoxy groups by UV irradiation, ester, urethane, olefin, and acrylic thermoplastic resins, and epoxy, melamine, and other thermosetting resins may be used.

[0176] (Step of removing deposits from a thin film having a functional layer)

[0177] The recycled film with a functional layer (i.e., the film with a functional layer that is the raw material of the recycled resin) has a functional layer provided on at least one surface of a substrate (i.e., a film substrate). That is, the film with a functional layer includes a substrate and a functional layer provided on at least one surface of the substrate. After using the film with a functional layer, there may be residual attachments on the surface of the film, for example, on the surface of the functional layer.

[0178] In addition, regarding the film with a functional layer, used films, films out of specification, films damaged during circulation, etc. are usually discarded. It is desirable that the process of removing the attached matter from such a film to be discarded (i.e., a film with a functional layer to be discarded) is performed as long as it does not damage the final film properties. In addition, the process of removing the attached matter may be omitted depending on the condition of the attached matter.

[0179] In the present invention, the step of removing the attached matter not only from the surface of the functional layer but also from the surface of the substrate opposite to the functional layer may be included. In addition, the step of removing the attached matter attached to the substrate may be included.

[0180] In another embodiment, the present invention provides a method for producing a laminated polyethylene terephthalate film for mold release. The method comprises the following (step 1), (step 2), and (step 3).

[0181] (Step 1) A pulverizing step including the step of pulverizing the laminated film having the functional layer to form a pulverized product.

[0182] (Step 2) A chipping step, which includes the step of chipping the pulverized product obtained in the above-mentioned step 1 into recycled chips.

[0183] (Step 3) A step of forming a recycled film, which includes forming the recycled small pieces obtained in the above-mentioned step 2 into a film and winding the above-mentioned film.

[0184] In the present invention, by including steps 1 to 3, even when no step of removing the deposits on the surface of the film having the functional layer is included, a laminated polyethylene terephthalate film for release can be obtained without impairing the physical properties of the recycled film.

[0185] (Pulverizing step of pulverizing the film)

[0186] (Step 1) A pulverizing step including the step of pulverizing the laminated film having the functional layer to form a pulverized product.

[0187] In the pulverizing step of the present invention, the pulverizing step can be performed without removing the attached matter on the surface of the thin film having the functional layer. For example, attached matter such as a binder, a ceramic green sheet, and impurities may also exist on the surface of the functional layer. In addition, a part of these attached matters may be removed before the pulverizing step is performed. By removing a part of the attached matters, the content of Si, Ti, and Ba components can be easily controlled.

[0188] In addition, for example, by the steps 2 and 3 described later, the contents of Si, Ti, and Ba components in the core layer C and the surface layer B can be controlled, so it is not necessary to completely remove the adhesive, ceramic green sheet, impurities, and other attachments present on the surface of the functional layer as in the conventional recycling technology. Moreover, the present invention does not need to remove the functional layer itself, but may remove a part of it in order to control the contents of Si, Ti, and Ba components.

[0189] The present invention can directly provide the functional layer and substrate with such attached materials to the crushing process. Therefore, compared with the previous recycling technology, the process and time required for the production and filming of resin pellets can be greatly reduced. In addition, the amount of waste can be reduced.

[0190] The present invention includes a pulverizing step as step 1, and the pulverizing step includes the step of pulverizing a laminated film having a functional layer to form a pulverized product. For example, it includes the step of pulverizing at least a substrate containing attachments to form a pulverized product. In one embodiment, the functional layer from which the attachments are removed can be further pulverized and then mixed with the pulverized product of the substrate. In the present invention, for the pulverized product obtained by pulverizing at least the substrate, the pulverized product of the functional layer from which the attachments are removed and the pulverized product of the substrate can be mixed. In addition, the pulverized product can be obtained in a state where the functional layer from which the attachments are removed is stacked with the substrate, or the functional layer from which the attachments are removed can be separated from the substrate and pulverized using the same pulverizer, or different pulverizers can be used to pulverize in other processes.

[0191] The film with a functional layer can be crushed using a pulverizer such as a single-axis pulverizer, a double-axis pulverizer, a triple-axis pulverizer, or a cutting mill. Specifically, a rotor having a plurality of rotating knives installed at a certain interval on the peripheral portion is accommodated in a housing equipped with a plurality of fixed blades, and solid materials are cut between the front end of each rotating knife rotated by the rotation of the rotor and the front end of the fixed knife, thereby crushing. Among the crushed materials, those that pass through a screen of a specified purpose are obtained as crushed materials. Any known method can be used as long as it is crushed in a manner of a specified size.

[0192] The pulverized product obtained by pulverizing in the pulverizing step is, for example, in the form of flakes, powders, blocks, or strips, but preferably includes flakes. In addition, the flake-shaped pulverized product refers to a thin flake and / or flat shape.

[0193] The size of the mesh hole used in the pulverizing process is preferably more than 1mm and less than 10mm, more preferably more than 3mm and less than 8mm. When the size of the mesh hole is less than 1mm, the pulverized product becomes powdery and difficult to handle, so it is preferably more than 1mm. In addition, if it is more than 10mm, the bulk density becomes too low, so it is difficult to control the discharge amount in the extrusion process described later, so it is preferably less than 10mm.

[0194] When the width of the film having the functional layer is narrow, for example, 20 mm or less, the film may be cut along the flow direction.

[0195] (Piecing process for producing recycled pieces)

[0196] (Step 2) A chipping step, which includes the step of chipping the pulverized product obtained in the above-mentioned step 1 into recycled chips.

[0197] The method for manufacturing the recycled small pieces is preferably to granulate the crushed material by melt extrusion. As the granulating device during the small pieces, a single screw extruder, a twin screw extruder, a multi-screw extruder, etc. can be cited. Preferably, a twin screw extruder or a multi-screw extruder that has both control of the mixing intensity and inhibition of resin degradation is used.

[0198] The granulated form may be any of cylindrical, pillow, spherical, and ellipsoidal.

[0199] The extrusion step of granulating the film into pellets may include a step of filtering the granules with a filter. By filtering the granules with a filter, coarse foreign matter that may cause the surface roughness of the obtained film to become rough can be removed. The step of filtering the granules with a filter may be repeated multiple times.

[0200] However, the laminated polyethylene terephthalate film in the present invention contains one or more Si, Ti, and Ba components, and the polyethylene terephthalate film contains the above-mentioned Si, Ti, and Ba components in a total amount of 0.1 ppm to 5000 ppm based on 100 parts by mass of the film. Therefore, Si, Ti, and Ba components cannot be completely removed.

[0201] (Thin film formation process)

[0202] (Step 3) A step of forming a recycled film, which includes forming the recycled small pieces obtained in the above-mentioned step 2 into a film and winding the above-mentioned film.

[0203] In one embodiment, the recycled chips obtained in step 2 can form the surface layer B and the core layer C.

[0204] In the present invention, by including recycled chips in the surface layer B and the core layer C, the surface layer A can have extremely high surface smoothness.

[0205] In one embodiment, the resin obtained by recycling the used film having a functional layer is a resin obtained by removing the functional layer and / or an object (e.g., a release material) attached to the functional layer. In addition, the substrate film before recycling, i.e., the film from which the functional layer is removed, may contain particles in an amount of 0.01 to 1.0 parts by mass, for example, 0.03 to 1.0 parts by mass, for example, 0.21 to 1.0 parts by mass, relative to 100 parts by mass of the film substrate before recycling.

[0206] By containing particles in such a range, in addition to the above-mentioned effects related to handling properties and surface roughness, the regenerated film, that is, the laminated polyethylene terephthalate film of the present invention can also have excellent rigidity, moisture resistance, and anti-blocking properties.

[0207] Although the explanation should not be limited to a specific theory, in the present invention, by making the base film have a predetermined amount of particles, not only the required operability and surface shape are achieved, but also additional functions such as rigidity can be well balanced. Therefore, for example, in the past, a process of removing particles treated as impurities was required, but in the present invention, as long as the haze and surface shape of the present invention are achieved, the active particle removal process can be omitted.

[0208] In one embodiment, the film from which the functional layer is removed may contain 0.01 to 1.0 parts by mass, for example, 0.21 to 1.0 parts by mass, of functional layer residues and residues attached to the functional layer, such as a demolding material, relative to 100 parts by mass of the film substrate before recycling. By containing the residues within such a range, the effect related to the surface roughness of the present invention can be achieved.

[0209] There are no particular limitations on the method for removing the above-mentioned residual attachments, and examples thereof include: a method of removing by sticking to an adhesive roller and peeling; a method of removing by vacuum suction; a method of scraping with a blade; a method of removing by high-pressure water or high-pressure air; a method of removing by blowing out sand or dry ice; a method of removing by immersing the film in a cleaning layer and adsorbing the attachments by microbubbles or the like; a method of removing by floating the attachments by microvibration such as ultrasound; a method of removing by dissolving the attachments by supercritical CO2, etc. These methods may also be combined.

[0210] These methods are not particularly limited, but a method that can be performed by roll-to-roll processing is preferred from the viewpoint of efficiency.

[0211] In this step, the functional layer may be removed together with the attached matter, or the functional layer may not be removed but may remain on the film.

[0212] Here, in the present invention, the process of removing the attached matter from the film having the functional layer includes the step of removing the adhesive, ceramic green sheet, impurities, etc. remaining on the surface of the functional layer. In addition, it can also be a process of removing the functional layer from the substrate. Preferably, the process of removing the attached matter is a process of removing the functional layer, such as a release layer and an easy-slip layer, from the substrate. By removing the functional layer, the recovery rate of the resin derived from the substrate film can be increased, and even in the recycled film after recycling, various physical properties that are not inferior to those of the substrate before recycling can be exhibited.

[0213] In one embodiment, the laminated polyethylene terephthalate film of the present invention comprises a resin obtained by separating a substrate portion from a used or unused film having a functional layer and recycling the substrate portion. For example, in the case of a release film used in the manufacture of a ceramic green sheet, it is preferred that the residue of the release object (green sheet) and the release layer are removed and the substrate portion is recycled.

[0214] In the present invention, the laminated polyethylene terephthalate film contains one or more Si, Ti, and Ba components, and the polyethylene terephthalate film contains a total of 0.1 ppm or more and 5000 ppm or less of Si, Ti, and Ba components relative to 100 parts by mass of the film. Therefore, as long as this condition is met, the film can be used in a recycling process in a state where residues of the demolded object (green sheet) and a demolding layer remain.

[0215] The method for biaxially stretching the polyester film in the present invention is not particularly limited, and a conventionally commonly used method can be used. For example, the polyester can be melted and extruded into a film by an extruder, and cooled by a rotating cooling drum to obtain an unstretched film, and the unstretched film can be biaxially stretched to obtain the film. The biaxially stretched film can be obtained by a method of biaxially stretching a uniaxially stretched film in the longitudinal or transverse direction successively in the transverse direction or in the longitudinal direction, or by biaxially stretching an unstretched film in the longitudinal and transverse directions simultaneously.

[0216] A filter may also be used during the period from when the recycled chips are melted to when they are extruded. The filter used in such filtration may be a filter known to itself according to the level of the target surface defects. Generally speaking, the smaller the 95% filtration accuracy (the particle size of the glass beads that cannot pass through and remain on the filter when the glass beads are passed), the smaller the foreign matter can be removed. Therefore, from the perspective of reducing the foreign matter that causes the tiny surface defects that are a problem in the present invention, the 95% filtration accuracy of the filter used is preferably 30 μm or less, and more preferably 20 μm or less. On the other hand, the smaller the 95% filtration accuracy, the more foreign matter can be removed, which means that foreign matter that cannot pass through the filter and is captured will accumulate faster. Moreover, if such foreign matter that cannot pass through the filter accumulates, when the thermoplastic resin is filtered, the amount of thermoplastic resin that can pass through the filter will also decrease, so that the amount when extruded into a sheet becomes unstable, or the filter cannot withstand the pressure of the thermoplastic resin to be extruded, and the captured foreign matter leaks out of the filter. Therefore, the lower limit of the 95% filtration accuracy of the filter is not limited, but is preferably 5 μm or more, and more preferably 10 μm or more. It should be noted that if the accumulated foreign matter leaks out, subsequent products become defective.

[0217] Such a filter for molten resin can also be placed in the period from the molten state when manufacturing the recycled chips to the extrusion. The filtration accuracy of the filter at this time can be appropriately selected according to the defect level in the target resin. It is preferred to select a filter size that does not remove particles necessary for film properties, such as particles for maintaining lubricity, and can remove aggregates of the functional layer that are not necessary for film properties.

[0218] The film-making method in the present invention is not limited. Specifically, after the material recycled polyester pellets are fully vacuum-dried, they are supplied to an extruder, melt-extruded into a sheet at about 255 to 280°C, and cooled and solidified to form an unstretched PET sheet. The obtained unstretched sheet is stretched to 3.0 times to 6.0 times in the length direction with a roller heated to 75°C to 140°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is gripped with a clamp and introduced into a hot air zone heated to 75°C to 140°C. After drying, it is stretched to 3.0 times to 6.0 times in the width direction. Next, a heat treatment zone of 180 to 260°C can be introduced for a heat treatment of 1 to 60 seconds. In this heat treatment process, a relaxation treatment of 0 to 10% can be performed in the width direction or the length direction as needed.

[0219] (resin sheet)

[0220] In one embodiment, the laminated polyethylene terephthalate film of the present invention can be used as a base material in a release film for molding a resin sheet.

[0221] As long as it is a resin sheet, there is no particular limitation, and it can be applied to the manufacture of adhesives and optical films. In one embodiment, it is a mold release film for resin sheet molding containing an inorganic compound. As the inorganic compound, metal particles, metal oxides, minerals, etc. can be exemplified, for example, calcium carbonate, silica particles, aluminum particles, barium titanate particles, etc. can be exemplified.

[0222] Examples of the resin include polyvinyl acetal resin and poly(meth)acrylate resin.

[0223] The laminated polyethylene terephthalate film of the present invention is suitable for laminating a release layer having high smoothness, and even when the resin sheet contains these inorganic compounds, it is possible to suppress the defects caused by the inorganic compounds, such as damage to the resin sheet and difficulty in peeling the resin sheet from the release layer.

[0224] The resin component forming the resin sheet can be appropriately selected depending on the intended use.

[0225] In one embodiment, the resin sheet containing an inorganic compound is a ceramic green sheet. For example, the ceramic green sheet may contain barium titanate as the inorganic compound. In one embodiment, the thickness of the resin sheet is 0.2 μm or more and 1.0 μm or less.

[0226] (Release film)

[0227] In one embodiment, the release film of the present invention comprises a laminated polyethylene terephthalate film and a release layer. The release layer is provided on the surface layer A of the laminated polyethylene terephthalate film. That is, the release film comprises a laminated polyethylene terephthalate film and a release layer laminated on the surface layer A of the laminated polyethylene terephthalate film.

[0228] The description of the release layer of the release film overlaps with the description of the release layer of the film having a functional layer (i.e., the recycled film having a functional layer) and is therefore omitted. Therefore, the description of the release layer of the film having a functional layer can also be treated as the description of the release layer of the release film of the present invention.

[0229] Example

[0230] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples. The characteristic values ​​used in the present invention were evaluated by the following methods.

[0231] (1) Intrinsic viscosity (IV)

[0232] Films (specifically, biaxially stretched polyethylene terephthalate films, recycled PET1 to 4, PET1, MB1) or polyester resins were pulverized and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). The solution was centrifuged to remove inorganic particles, and then the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of only the solvent were measured using an Ubbelohde viscometer. From the ratio of these time periods, the intrinsic viscosity was calculated using the Huggins formula, assuming that the Huggins constant was 0.38.

[0233] (2) Si and Ti analysis

[0234] As a pretreatment, about 1 g of a sample (specifically, biaxially stretched polyethylene terephthalate film, recycled PET1 to 4, PET1, MB1) was taken, 15 ml of nitric acid, 3 ml of ultrapure water, and 0.1 ml of hydrofluoric acid were added, and the sample solution was converted into acid using a microwave sample decomposition device (UltraWAVE manufactured by Milestone General KK). Then, the Si element content and the Ti element content were measured using an ICP emission analyzer (SPECTRO BLUE TI manufactured by SPECTRO).

[0235] (3)Ba analysis

[0236] As a pretreatment, about 0.5 g of a sample (specifically, biaxially stretched polyethylene terephthalate film, recycled PET1 to 4, PET1, and MB1) was collected, carbonized / ashed, and the residue was dissolved in 1.2 N hydrochloric acid to prepare a sample for measurement. Then, the Ba element content was measured using an ICP emission spectrometer (SPECTRO BLUE TI manufactured by SPECTRO).

[0237] (4) Surface roughness (SRa, SRp)

[0238] For the outermost layer (specifically, A layer) surface of the biaxially stretched polyethylene terephthalate film, a stylus-type three-dimensional roughness meter (SE-3AK, manufactured by Kosaka Laboratory Ltd.) was used. Under the conditions of a needle radius of 2 μm and a load of 30 mg, the biaxially stretched polyethylene terephthalate film was measured with a cutoff value of 0.25 mm, a measurement length of 1 mm, and a needle feed speed of 0.1 mm / second. The film was divided into 500 points at a 2 μm interval, and the height of each point was introduced into a three-dimensional roughness analyzer (SPA-11). The same operation was continuously performed 150 times at 2 μm intervals in the width direction of the biaxially stretched polyethylene terephthalate film, that is, 0.3 mm in the width direction of the biaxially stretched polyethylene terephthalate film was performed, and the data was introduced into the analyzer. Next, the center plane average roughness (SRa) and the center line peak height (SRp) were obtained using the analyzer.

[0239] (5) Average particle size

[0240] The surface roughening agent was observed using a scanning electron microscope (S-510 manufactured by Hitachi, Ltd.), and the magnification was appropriately changed according to the size of the particles, and the photograph was enlarged and copied. Next, for at least 200 particles selected randomly, the periphery of each particle was tracked, and the equivalent circle diameter of the particles was measured from these tracked images using an image analyzer, and their average was taken as the average particle size.

[0241] (6) MLCC processability evaluation

[0242] After forming a silicone-based release layer as a functional layer on a biaxially stretched polyethylene terephthalate film of interest, a ceramic green sheet (MLCC) was produced, and the defect rate caused by the biaxially stretched film was evaluated. Specifically, the defect rate was evaluated according to the following procedure.

[0243] (Production of release film)

[0244] On the A layer of the biaxially stretched polyethylene terephthalate film, the coating film thickness (wet weight) was 5 g / m 2 The coating solution described later was applied by reverse gravure coating, and then dried at 100°C for 2 seconds 0.5 seconds after coating (hereinafter sometimes referred to as "initial drying"). After heating at 130°C for 7 seconds without intervals from initial drying (i.e., continuous from initial drying), the heating was terminated and the film was wound into a roll after 8 seconds. Thus, 100 release films were prepared in each example.

[0245] (Coating liquid for making release film)

[0246] The composition of the coating liquid used to prepare the release film is as follows: The solid content of the coating liquid is 1.0% by mass, the surface tension is 27 mN / m, and the viscosity is 5 mPa·s. It should be noted that the coating liquid was used after passing through a filter that can remove more than 99% of foreign matter larger than 0.5 μm.

[0247] Methyl ethyl ketone 57.93 parts by mass

[0248] Toluene 40.00 parts by mass

[0249] Resin solution A (40% by weight of a long-chain alkyl-containing acrylic polyol solution. The preparation method will be described later.) 1.75 parts by weight

[0250] Crosslinking agent (hexamethoxymethylolmelamine, solid content 100% by mass) 0.25 parts by mass

[0251] Silicone release agent (polyether-modified polydimethylsiloxane, TSF4446, solid content 100% by mass, manufactured by Momentive) 0.05 parts by mass

[0252] Acid catalyst (p-toluenesulfonic acid) 0.02 parts by mass

[0253] (Preparation of Resin Solution A)

[0254] After mixing them in a ratio of 20 mol% of stearyl (meth)acrylate, 40 mol% of hydroxyethyl (meth)acrylate, and 40 mol% of methyl (meth)acrylate, the mixture was diluted with toluene so that the solid content concentration became 40% by mass, and 0.5 mol% of azobisisobutyronitrile was added under a nitrogen stream to copolymerize the mixture. Thus, a resin solution A (i.e., a long-chain alkyl-containing acrylic polyol solution) having a solid content of 40% by mass was obtained. The weight average molecular weight of the polymer obtained at this time was 30,000.

[0255] (Production of ceramic green sheets)

[0256] The following materials were stirred and mixed, and then dispersed for 60 minutes using a bead mill using zirconia beads having a diameter of 0.5 mm as a dispersant, thereby obtaining a ceramic slurry.

[0257] Toluene 43.75 parts by mass

[0258] Ethanol 43.75 parts by mass

[0259] Barium titanate (HPBT-1 manufactured by Fuji Titanium Co., Ltd.) 10.86 parts by mass

[0260] Polyvinyl butyral (S-LEC BM-S manufactured by Sekisui Chemical Co., Ltd.) 1.09 parts by mass

[0261] DOP (dioctyl phthalate) 0.55 parts by mass

[0262] The ceramic slurry was applied to the release layer of the release film using an applicator so that the thickness of the ceramic green sheet was 1.0 μm, and then dried at 90° C. for 2 minutes. In this way, a ceramic green sheet was produced on the release film. In each example, 100 ceramic green sheets were produced.

[0263] (Good or bad judgment)

[0264] After the ceramic green sheet is peeled off from the release film, the arithmetic mean roughness Ra and the maximum protrusion height Rp of the peeled surface of the ceramic green sheet (i.e., the surface of the ceramic green sheet in contact with the release film) are measured, and the quality is judged according to the following criteria. It should be noted that the measurement of Ra and Rp uses a scanning white interference microscope "VertscanVS1530" manufactured by Hitachi High-Technologies Corporation.

[0265] Good Ra is less than 8nm and Rp is less than 50nm

[0266] Defective Ra is 8nm or more or Rp is 50nm or more

[0267] (Calculation of defective rate)

[0268] The defective rate of each case was calculated using the following formula.

[0269] Defective rate (%)

[0270] =(number of ceramic green sheets judged as defective / 100 sheets)×100

[0271] The defective rate of each example is shown in Table 3 according to the following classification.

[0272] ○Defective rate less than 3%

[0273] △Defective rate is more than 3% and less than 5%

[0274] ×Defective rate exceeds 5%

[0275] (Preparation of recycled PET1)

[0276] A used PET film having a silicone release layer on one surface and containing 600 ppm of calcium carbonate with a particle size of 1.0 μm was used. The film was pulverized using a 4 mm mesh screen at a speed of 100 kg / hour using a single-axis pulverizer to obtain a pulverized film. The obtained pulverized film was fed into a twin-screw extruder to obtain recycled PET1. The intrinsic viscosity of the recycled PET1 was 0.56 dl / g, and the Si concentration was 200 ppm. The evaluation results and various conditions are shown in Table 1.

[0277] (Preparation of recycled PET2)

[0278] A used PET film having a non-silicone release layer (containing amino acrylic resin as the main component) on one surface and containing 600 ppm of calcium carbonate with a particle size of 1.0 μm was used. The film was crushed using a 4 mm mesh screen at a speed of 100 kg / hour using a single-axis crusher to obtain a crushed film. The obtained crushed product was put into a twin-screw extruder to obtain recycled PET2. The intrinsic viscosity of the recycled PET2 was 0.56 dl / g, and the Si concentration was 5 ppm. The evaluation results and various conditions are shown in Table 1.

[0279] (Preparation of recycled PET3)

[0280] A used PET film having a silicone release layer on one surface and containing 600 ppm of calcium carbonate with a particle size of 1.0 μm is prepared. The PET film is a PET film used in the manufacture of ceramic green sheets. The silicone release layer is removed from the PET film by sandblasting (of course, for the sake of caution, impurities attached to the silicone release layer are also removed as the silicone release layer is removed). The film from which the silicone release layer has been removed is pulverized using a 4 mm mesh screen at a speed of 100 kg / hour using a single-axis pulverizer to obtain a pulverized film. The obtained pulverized product is fed into a twin-screw extruder to obtain recycled PET3. The intrinsic viscosity of the recycled PET3 is 0.57 dl / g, and the Si concentration is 5 ppm. The evaluation results and various conditions are shown in Table 1.

[0281] (Preparation of recycled PET4)

[0282] A used PET film having a silicone release layer on one surface and containing 600 ppm of calcium carbonate with a particle size of 1.0 μm was used. The PET film is a PET film used in the manufacture of ceramic green sheets. The film was pulverized using a 4 mm hole screen at a speed of 100 kg / hour using a single-axis pulverizer to obtain a pulverized film. The obtained pulverized product was put into a twin-screw extruder to obtain recycled PET4. The intrinsic viscosity of the recycled PET4 is 0.56 dl / g, the Si concentration is 200 ppm, the Ti concentration is 50 ppm, and the Ba concentration is 150 ppm. The evaluation results and various conditions are shown in Table 1.

[0283] (Preparation of polyethylene terephthalate particles (PET1))

[0284] As the esterification reaction apparatus, a continuous esterification reaction apparatus consisting of a three-stage complete mixing tank having a stirring device, a fractionator, a raw material inlet and a product outlet was used. TPA was set to 2 tons / hour, EG was set to 2 mol relative to 1 mol of TPA, and antimony trioxide was set to an amount of 160 ppm of Sb atoms relative to the generated PET. These slurries were continuously supplied to the first esterification reaction tank of the esterification reaction apparatus, and the reaction was carried out at 255°C under normal pressure with an average residence time of 4 hours.

[0285] Next, the reaction product in the first esterification reaction tank was continuously taken out of the system and supplied to the second esterification reaction tank, and EG distilled from the first esterification reaction tank was supplied to the second esterification reaction tank in an amount of 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount of 65 ppm of Mg atoms relative to the produced PET and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the produced PET were added, and the mixture was reacted at 260° C. at an average residence time of 1.5 hours under normal pressure. Next, the reaction product in the second esterification reaction tank was continuously taken out of the system and supplied to the third esterification reaction tank, and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the produced PET was further added, and the mixture was reacted at 260° C. at an average residence time of 0.5 hours under normal pressure. The esterification reaction product generated in the third esterification reaction tank was continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, and then filtered with a stainless steel sintered body filter (nominal filtration accuracy 5 μm particles 90% split) to obtain PET (I) (also referred to as "PET1" in this specification) as polyethylene terephthalate particles with an intrinsic viscosity of 0.62 dl / g. The evaluation results and various conditions are shown in Table 1.

[0286] (Preparation of Polyethylene Terephthalate Calcium Carbonate Masterbatch (MB1))

[0287] The above PET (I) and calcium carbonate particles having an average particle size of 1.0 μm were melt-kneaded using a twin-screw extruder to prepare a masterbatch having a calcium carbonate particle concentration of 20,000 ppm. The evaluation results and various conditions are shown in Table 1.

[0288] (Example 1)

[0289] Each of the above PETs was dried, melted at 285°C, melted at 290°C by a separate melt extruder, filtered in two stages by a filter having 95% of sintered stainless steel fibers with a split diameter of 15 μm and a filter having 95% of sintered stainless steel particles with a split diameter of 15 μm, merged in a feed block, and laminated in such a manner that PET1 is 75% and MB1 is 25% as a B layer (anti-release surface side layer), PET1 is an A layer (release surface side layer), and PET1 is 60% and recycled PET1 is 40% as a C layer, extruded (casting) at a speed of 45 m / min into a sheet, and electrostatically bonded / cooled on a casting drum at 30°C by an electrostatic bonding method to obtain an unstretched polyethylene terephthalate sheet with an intrinsic viscosity of 0.56 dl / g. The layer ratio (i.e., thickness ratio) was adjusted to A layer / C layer / B layer = 40% / 40% / 20% by calculating the discharge amount of each extruder.

[0290] The electrostatic adhesion conditions at this time were as follows: the electrode material was tungsten, cylindrical (wire) with a diameter of 0.2 mm and a length of 0.5 m, the current was constantly controlled at 5 mA, the tension of the electrode was 5 kg, and the renewal speed of the electrode was 5 m / hour.

[0291] Next, the unstretched polyethylene terephthalate sheet was heated with an infrared heater and stretched 3.5 times in the longitudinal direction at a roller temperature of 80° C. using the speed difference between the rollers. Then, it was introduced into a tenter and stretched 4.2 times in the transverse direction at 140° C. Next, it was heat treated at 210° C. in a heat setting zone. Then, it was relaxed by 2.3% in the transverse direction at 170° C. to obtain a mill roll (width 5.0 m) of a biaxially stretched polyethylene terephthalate film having a thickness of 31 μm.

[0292] The calender roll was moved to a cutter, treated with a destaticizer (manufactured by KASUGADENKI, INC., high-density destaticizer system) and a web cleaner (manufactured by SHINKO CO,.LTD., ultrasonic cleaner system), and then cut into 1400 mm widths. The roll was wound at a maximum speed of 400 m / min with a contact surface pressure of 200 kg / m and a tension of 15 MPa on a core material with resin-impregnated paper having an inner diameter of 6 inches, a wall thickness of 12 mm, a moisture content of 8%, a surface roughness of 4.3 nm, SRp of 41.4 nm, and a flat compression strength of 200 kg / 100 mm using a contact roll having a rubber hardness of 60 degrees, and a length of 8000 m to obtain a biaxially stretched polyethylene terephthalate film roll. A biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0293] It should be noted that the dust level of the atmosphere in the thin film production process was Class 1000.

[0294] (Examples 2 and 3)

[0295] The raw material formulation of the C layer was changed from that of Example 1 to obtain the biaxially stretched polyethylene terephthalate film roll shown in Table 2. The biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0296] (Example 4)

[0297] The raw material of the C layer in Example 1 was changed from recycled PET1 to recycled PET2 to obtain the biaxially stretched polyethylene terephthalate film roll shown in Table 2. The biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0298] (Example 5)

[0299] The raw material of the C layer in Example 1 was changed from PET1 to recycled PET4 to obtain the biaxially stretched polyethylene terephthalate film roll shown in Table 2. The biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0300] (Example 6)

[0301] The layer ratio (i.e., thickness ratio) was changed from Example 1 as shown in Table 2 to obtain a biaxially stretched polyethylene terephthalate film roll as shown in Table 2. A biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0302] (Example 7)

[0303] The layer structure was changed to two layers of A / B from Example 1, and the raw material of the B layer was changed from PET1 to recycled PET3, and a biaxially stretched polyethylene terephthalate film roll shown in Table 2 was obtained. A biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0304] (Comparative Example 1)

[0305] The raw materials were changed from Example 1 as shown in Table 2 to obtain the biaxially stretched polyethylene terephthalate film roll shown in Table 2. The biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0306] (Comparative Example 2)

[0307] The raw material formula of the B layer was changed from that of Example 7 to obtain the biaxially stretched polyethylene terephthalate film roll shown in Table 2. The biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0308] (Comparative Examples 3 and 4)

[0309] The layer ratio (i.e., thickness ratio) was changed from Example 1 as shown in Table 2 to obtain a biaxially stretched polyethylene terephthalate film roll as shown in Table 2. A biaxially stretched polyethylene terephthalate film was cut out from the biaxially stretched polyethylene terephthalate film roll and various evaluations were performed. The evaluation results are shown in Tables 2 and 3.

[0310] MLCC was produced using the biaxially stretched polyethylene terephthalate film of the example, and the defective rate caused by the biaxially stretched polyethylene terephthalate film was evaluated. As a result, the defective rate was suppressed to 3% or less, and a good processed product was obtained.

[0311] Furthermore, by using recycled film, environmentally friendly products (specifically, biaxially stretched polyethylene terephthalate film and release film) can be manufactured. For example, it is possible to exhibit performance equivalent to that of the biaxially stretched polyethylene terephthalate film of Comparative Example 2 (i.e., biaxially stretched polyethylene terephthalate film without using recycled PET 1 to 4).

[0312] In Comparative Example 1, the three-dimensional center plane average surface roughness (SRa) and the maximum peak height (SRp) of the surface layer A were outside the range of the present invention, and the moldability of the MLCC was insufficient.

[0313] Comparative Example 2 does not contain Si, Ti, or Ba components and is outside the scope of the present invention. In addition, recycled PET 1 to 4 are not used, which does not contribute to reducing environmental load.

[0314] The three-dimensional center plane average surface roughness (SRa) and the maximum peak height (SRp) of Comparative Examples 3 and 4 exceeded the range of the present invention, and the moldability of MLCC was insufficient.

[0315] [Table 1]

[0316]

[0317] [Table 2]

[0318]

[0319] In addition, in Table 2, "MB" represents a polyethylene terephthalate calcium carbonate masterbatch, that is, MB1.

[0320] [Table 3]

[0321]

[0322] Industrial Applicability

[0323] The present invention can provide a laminated polyethylene terephthalate film, a release film, and a method for producing a laminated polyethylene terephthalate film, and therefore has industrial applicability.

Claims

1. A laminated polyethylene terephthalate film comprising a surface layer A and a surface layer B, The laminated polyethylene terephthalate film contains one or more of Si, Ti and Ba components. The total amount of Si element, Ti element and Ba element is 0.1 ppm or more and 5000 ppm or less relative to 100 parts by mass of the laminated polyethylene terephthalate film, The surface layer A is a layer on which the functional layers are stacked, and the three-dimensional center plane average surface roughness (SRa) of the surface layer A is 1 nm to 7 nm, and the maximum peak height (SRp) of the surface layer A is 200 nm or less. 2 . The laminated polyethylene terephthalate film according to claim 1 , comprising 5% by mass or more and 50% by mass or less of a resin obtained by material recycling and / or chemical recycling of a laminated film having a functional layer.

3. The laminated polyethylene terephthalate film according to claim 1, wherein: The laminated polyethylene terephthalate film contains SiO 2 having a longest side length of 0.5 μm or more and 5.0 μm.

4. The laminated polyethylene terephthalate film according to claim 1, wherein: The surface layer B is a layer forming a surface of the laminated polyethylene terephthalate film opposite to a surface on which the functional layer is laminated. The surface layer B contains at least one particle selected from calcium carbonate particles or silicon dioxide particles in a total amount of 3000 ppm or more and 15000 ppm or less relative to 100 parts by mass of the laminated polyethylene terephthalate film, The three-dimensional center plane average surface roughness (SRa) of the surface layer B is 20 nm or more and 40 nm or less. 5 . The laminated polyethylene terephthalate film according to claim 1 , which has an intrinsic viscosity (IV) of 0.500 dl / g or more and 0.700 dl / g or less.

6. The laminated polyethylene terephthalate film according to claim 1, wherein: The thickness ratio of the surface layer A is 30% or more and 50% or less of all layers.

7. A release film comprising: The laminated polyethylene terephthalate film according to claim 1; and The functional layer provided on the surface layer A of the laminated polyethylene terephthalate film, The functional layer is a release layer.

8. A method for producing a laminated polyethylene terephthalate film according to any one of claims 1 to 6, comprising the following steps: (Step 1) a pulverizing step, comprising the step of pulverizing the laminated film having the functional layer to form a pulverized product; (Step 2) a flake-forming step, which includes the step of flake-forming the pulverized product obtained in the step 1 to form recycled flakes; (Step 3) A step of forming a recycled film, which includes forming the recycled small pieces obtained in the step 2 into a film and winding the film.

Citation Information

Patent Citations

  • Reclamation method of film and regenerated film

    JP2021115862A

  • Polyester, composition thereof and film thereof

    WO2008096612A1

  • Roll of laminated polyethylene terephthalate film for release use

    JP2007062179A

  • Biaxially orientated polyester film for mold release and method of producing the same

    JP2014133373A

  • Laminated polyester film

    JP2016187963A